Analytical Review of the Common Failures of Satellite Structures: Causes, Effects, and Mitigation Strategies - Kazem Reza Kashyzadeh; Sergei A. Kupreev; Oleg E. Samusenko (RUDN Journal of Engineering Research)
Satellite structures are subjected to extreme conditions throughout their operational lifespan, including high launch loads, thermal cycling, and space debris impacts, making them vulnerable to structural failures. Understanding the causes, effects, and mitigation strategies for such failures is crucial for enhancing satellite reliability and mission success. This review critically examines the common structural failures in satellites, categorizing them by affected components such as primary frames, joints, thermal shielding, and deployable mechanisms. The study employs a comprehensive analysis of historical and recent failures, integrating insights from case studies, experimental research, and advancements in materials science and structural health monitoring. The findings highlight key failure mechanisms, including material fatigue, vibrational stresses, and thermal degradation, and assess innovative solutions such as smart materials and in-orbit repair techniques. By synthesizing current research and industry practices, this review provides a systematic understanding of failure trends and proposes future directions for improving satellite structural resilience. The insights presented in this study aim to support the development of more robust satellite architectures, ultimately contributing to safer and more reliable space missions.